SYSTEM OF EVALUATION OF THE ENVIRONMENTAL COSTS OF THE THERMAL GENERATION IN PERU - Author (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
It is necessary to analyze the advantages and disadvantages of the use of electricity generation with renewable energy resources and fossil fuels, that is, the environmental costs derived from greenhouse gas emissions emitted by thermal generation in Peru. Since when environmental, social and economic costs generated by thermal power plants begin to be quantified, we realize that damage to health and the environment is caused. In this context, a system for evaluating the environmental costs of thermal generation in Peru is necessary, whose result must be an integral part for the calculation of the variable costs of thermoelectric generation units allowing the internalization of environmental costs, mainly those associated with greenhouse gas emissions, which will make it possible to reorder the generation dispatch ranking of the thermoelectric generation units of the National Interconnected Electric System prepared by COES; for which, as an example of the study, the proposed evaluation system for thermal power plants using Camisea natural gas is applied.